Equity of maternal and child health services in Afghanistan: a spatiotemporal analysis of national survey datasets - Groteclaes, Tim Tobias; Ahmed, Saifuddin; Blumenberg, Cauane; Barros, Aluisio J. D.; Chopra, Mickey; Akseer, Nadia (BMJ global health, 2025)
Introduction Afghanistan’s healthcare system faces geopolitical instability and inequities in maternal and child health (MCH) services, particularly associated with a temporary collapse in funding in 2021. We analysed coverage levels and spatiotemporal trends in sociodemographic inequalities in the country using data from the 2010/2011 and 2022/2023 Afghan Multiple Indicator Cluster Surveys.Methods The study’s primary outcome was an adapted Composite Coverage Index (CCI) that combined seven essential MCH interventions with corresponding inequality measures, evaluated using Slope Indices of Inequality. These interventions included antenatal care, skilled birth attendance (SBA), Bacillus-Calmette-Guérin (BCG), diphtheria-pertussis-tetanus, and measles vaccination and treatment for suspected pneumonia and diarrhoea. Inequalities were analysed across wealth, education and urban/rural status at both national and provincial levels.Results The analysis revealed persistent socioeconomic inequalities across all strata, with the most significant economic disparities observed in SBA and the largest educational disparities in vaccine coverage in 2022/2023. Nationally, the CCI increased by 4.2% from 42.1% (95% CI 40.3% to 44%) in 2010/2011 to 46.2% (95% CI 44.6% to 47.9%) in 2022/2023. Despite a slight increase between the two studies, severe regional disparities are masked, particularly in the eastern and southern regions, where coverage across multiple interventions significantly declined. The provinces of Nooristan and Urozgan significantly lost coverage, while Daykundi and Nimroz recorded increases in coverage and equity.Conclusion The findings underscore the persistence of substantial inequalities in Afghanistan, with severe consequences for already vulnerable populations facing multiple hardships. The findings highlight ways in which geopolitical instability affects healthcare equity. Increasing disparities threaten to exacerbate existing challenges in accessing essential healthcare services, particularly for those of lower socioeconomic status. Urgent, targeted interventions are necessary to address these inequities, the impacts associated with funding cuts and gender marginalisation, and to mitigate their detrimental impact on Afghan women and children.